Intelligent health consultant using expert system based on body mass index / Nurhayati Zakaria - Zakaria, Nurhayati (2014)
In this paper, the researcher analyze the application about healthy body is very important to maintain healthy body. It is important because people are face with problem to meet the dietitian to get advice regular basis every week for any related issues about healthy lifestyle. In this research will focused on developing mobile application that can save information and health history of the users and to develop an Android mobile application to give consultation for those who are very concerned about health using rule-based expert system. It was significant for people to know the healthy body status according to calculation of Body Mass Index (BMJ). This application was different with existing application because it include about history of health information using on line database. It can be save and retrieve back using online database that can save many data and it is not overload to the phone memory. This application will guide the people to manage their eating planning to maintain their body weight and healthy body. The suggestion menu is based on five meals in daily life that is breakfast, morning snack, lunch, afternoon snack and dinner. The range of total calories for each category of BMI and food suggestion was validated by expert dietitian. However, this application is only a tool to help people manage their health but it depend on that person personally to manage their health and how effectiveness of this application for themselves.